Peculiarities of Training Future Physical Education Specialists in Physiology under Martial Law - Ruda, Vira (Pedagogical Discourse, 2025)
The article reveals the content and features of studying the academic discipline «Physiology» by students of the specialty 014.11 Secondary education (physical education). The purpose is to reveal the features of training future physical education specialists in physiology under martial law at the Khmelnytskyi Humanitarian-Pedagogical Academy. The study used theoretical and empirical research methods. Theoretical methods include: analysis of modern scientific and methodological literature, synthesis, generalization, abstraction, induction, deduction, etc. Empirical research methods included: survey, direct and indirect observation, modeling of practical activities, which were aimed at analyzing the practical activities of future physical education teachers. It has been established that teaching the academic discipline «Physiology» was based on the study of physiological processes that occur in school-age children during physical exercises. The training of future qualified physical education specialists is based on a combination of theoretical knowledge and practical skills that are necessary for organizing the educational process in a general secondary education institution. The main didactic goal of practical classes is to expand, deepen and detail the scientific knowledge obtained by students in lectures and in the process of independent work. Military operations on the territory of Ukraine, frequent air raids have a negative impact on the organization of education in higher education institutions. In such conditions, teachers are forced to be flexible and provide additional assistance to students in mastering the educational material, combining distance and traditional forms of learning. The system of organizing the educational process at the Khmelnytsky Humanitarian-Pedagogical Academy allows students of the specialty 014.11 Secondary Education (Physical Culture) to achieve program learning outcomes in the discipline «Physiology».